2016
DOI: 10.1189/jlb.4a0616-271r
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between T helper cells, iNKT cells, and their follicular helper subsets in the humoral immune response against Clostridium difficile toxin B

Abstract: Activation of iNKT cells with the CD1d-binding glycolipid adjuvant α-galactosylceramide (α-GC) enhances humoral immunity specific for coadministered T-dependent Ag. However, the relationship between the iNKT cell and the classic T helper (Th) or T follicular helper (Tfh) function following this immunization modality remains unclear. We show that immunization with the C-terminal domain (CTD) of Clostridium difficile toxin B (TcdB), accompanied by activation of iNKT cells with α-GC, led to enhanced production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Similar to the development of conventional Tfh cells, the formation of NKTfh cells is dependent on CD28-mediated cognate interactions with B cells and Bcl6 expression ( 196 ). Studies utilizing CD4 + T cell-specific loss of Bcl6 determined that both Tfh and iNKTfh cells contribute to B cell help ( 197 ). However, unlike Tfh-derived B cell responses, those driven by NKTfh cells have no potential to generate long-lived plasma cells and memory B cells ( 196 ).…”
Section: Other Follicular T Cellsmentioning
confidence: 99%
“…Similar to the development of conventional Tfh cells, the formation of NKTfh cells is dependent on CD28-mediated cognate interactions with B cells and Bcl6 expression ( 196 ). Studies utilizing CD4 + T cell-specific loss of Bcl6 determined that both Tfh and iNKTfh cells contribute to B cell help ( 197 ). However, unlike Tfh-derived B cell responses, those driven by NKTfh cells have no potential to generate long-lived plasma cells and memory B cells ( 196 ).…”
Section: Other Follicular T Cellsmentioning
confidence: 99%
“…Stimulation of iNKT cells isolated from the pleural fluid of humans with tuberculosis with Mycobacterium tuberculosis antigens results in their expression of CXCR5, release of IL-21 and the provision of cognate B cell help for the production of IgG and IgA ( 64 ). Both T FH and iNKT FH cells contribute to B cell help and the production of antibodies to Clostridium difficile toxin B in mice ( 65 ). Furthermore, CD1d expression by B cells was required for iNKT cell-mediated B cell help to a protein antigen in mice co-immunized with a mixture of the protein antigen and α-GalCer, indicating that cognate iNKT cell–B cell interactions can play a role in the development of antibody responses to protein antigens ( 53 ).…”
Section: Inkt Cells Can Provide Cognate B Cell Helpmentioning
confidence: 99%
“…Fewer studies have addressed whether there is direct communication between Th/Tfh and NKT/NKT follicular helper cells (NKTfh) cells during a humoral response. Our studies showed a temporal relationship between Th/Tfh and NKT/NKTfh production of IL-4 and IL-21, with the NKT/NKTfh compartments providing an early source of IL-21 ( 27 ). However, we did not detect any direct dependence of one cell type upon the other with regard to cytokine secretion.…”
Section: Mechanisms Regulating Nkt Cell Influence On T-dependent Humomentioning
confidence: 74%
“…This phenomenon explains the previous identification of an IL-21-secreting NKT subset ( 59 ), which is now known to express high levels of the master transcriptional regulator Bcl6, and upregulate the chemokine receptor CXCR5, and the PD1 molecule. The NKT subset may provide an early source of IL-21 ( 27 ) and perhaps accelerate Ig class switch, an effect that may have been missed in earlier studies examining cytokine contributions ( 3 ). The NKT-enhanced IgG response to T-dependent Ag is typically IgG1-dominated and this makes sense given the pivotal role of Tfh-derived IL-21 in IgG1 class switch ( 60 , 61 ).…”
Section: Mechanisms Regulating Nkt Cell Influence On T-dependent Humomentioning
confidence: 99%